2020
DOI: 10.1080/19475705.2020.1789762
|View full text |Cite
|
Sign up to set email alerts
|

An investigation on seasonal variability between LST and NDWI in an urban environment using Landsat satellite data

Abstract: The urban landscape is considered the most complex and heterogeneous landscape among the different land surface features. It rises the land surface temperature (LST) to a large extent compared to the surrounding rural body. This investigation deals with the seasonal variability between LST and normalized difference water index (NDWI) on the different land surfaces in Raipur, India by using sixty-four Landsat images from 1991-92 to 2018-19. The results show that the post-monsoon season indicates the best correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(23 citation statements)
references
References 71 publications
(81 reference statements)
4
19
0
Order By: Relevance
“…Generally, the nature of LST-NDWI relationship in an urban area is insignificant which is controlled by several factors, such as humidity, vegetation, wetland, bare land, air pollution, rock surface, dry or wet soil, heterogeneous man-made materials, etc. (McFeeters 1996;Ghobadi et al 2014;Guha et al 2020c).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the nature of LST-NDWI relationship in an urban area is insignificant which is controlled by several factors, such as humidity, vegetation, wetland, bare land, air pollution, rock surface, dry or wet soil, heterogeneous man-made materials, etc. (McFeeters 1996;Ghobadi et al 2014;Guha et al 2020c).…”
Section: Introductionmentioning
confidence: 99%
“…Later, accuracy evaluation was applied to obtain the NDWI 's transparent pixel value. In addition, validation of the kappa coefficient, overall precision, and accuracy was carried out (Guha et al, 2020;Khine et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…In Southern Bangladesh, thousands of speople have lost their ability to make a proper living just because of waterlogging, particularly poor and landless farmers, share-holders, daily wage laborers, small traders, and others (Shaibur et al, 2019). Various previous studies have shown that GIS and RS techniques are useful for detecting and mapping waterlogged areas for different study areas (Guha et al, 2020;Hassan & Mahmud-ul-islam, 2014;Khine et al, 2018;Mahmud et al, 2017;Sar et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The inverse relationship of LST with the NDVI and the NDWI determined in these studies suggests that vegetation has a mitigative effect on the surface urban heat island. However, studies dealing with large spatial and/or temporal scales have reported contradictive results regarding the relationship between LST and land cover characteristics, depending on the year, season, time of the day or geographic location [20][21][22][23][24]. This indicates the complexity of this relationship and the importance of its continuous monitoring at a local level.…”
Section: Introductionmentioning
confidence: 99%